Edupreneur Clinic Based on Life Skill 5.0: Entrepreneurial Interest Enhancement Program for Student in Malang - Kusdiyanti, Heny; Sopingi, Sopingi; Zandra, Rully Aprilia; Anggarani, Dinar Arsy; Agustina, Nur Indah; Sulfa, Devi Mariya (STKIP Singkawang, 2024)
The Life Skills 5.0 Based Edupreuner Clinic Program in Malang Raya aims to develop young entrepreneurs in junior high schools. With a holistic approach, this program includes training, coaching by experienced entrepreneurs, life skills, and business exhibitions. The program strategy uses P4 (Preparation, Media Completion, Program Implementation, Evaluation Reporting). The advantage of this program lies in increasing partners' knowledge and skills in entrepreneurship. The results show significant improvements, including knowledge, entrepreneurial ability, entrepreneurial excellence, and the number of students starting entrepreneurship. The program can collaborate with local industry and financial institutions, helping students understand market needs and financial resources. Focusing on fostering young entrepreneurs plays an important role in economic growth and creating job opportunities. Overall, this program creates an entrepreneurial culture among junior high school students, producing a generation of entrepreneurs who are innovative, resilient and have a positive impact in Greater Malang.